Dampak Kualitas Auditor dalam Pengungkapan Emisi Karbon Terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode 2019-2022 - Tiara Rani Santoso; Rahel ezra (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aimed to test and analyze the effect of carbon emission disclosure and enviromental performance on firm value with audit quality as a moderating variable. Carbon emission disclosure is measured by calculating the carbon emission disclosure checklist index, enviromental performance is obtained from secondary data from the Indonesian Ministry of Envirement’s PROPER report, firm value is measured by Tobin’s Q, and audit quality is measured by the size of KAP. The sample was taken using a purposive sampling technique totaling 28 non-financial companies listed on the IndonesiaStock Exchange (IDX) for teh 2019-2022 period and having a PROPER rating for the 2019-2022 period. The data analysis technique used Structural Equation Modeling Partial Least Square (SEM-PLS) analysis with the help of the WarpPls 7.0 program. The result of the study indicate that: 1) There is a positive effect of carbon emission disclosure on firm value. 2)There is a positive effect of enviromental performance on firm value. 3) Audit quality does not moderate the effect of carbon emission disclosure on firm value. 4) Audit quality does not moderate the effect of enviromental performance on firm value.